Anxiety disorders: the new achievements - Kalinin, Vladimir V. (Intech Open, 2021)
This book is organized into three sections containing chapters related to multifarious problems of anxiety. In the first section, chapters are related to various social aspects of anxiety. The second section includes data on clinical aspects of anxiety and some other psychopathological syndromes in which anxiety may be evident. It also presents the psychopathology of Capgras syndrome and de Clerambault’s syndrome. The third section includes chapters related to neurobiological data and the pathogenesis of anxiety disorders. The section also presents results of immunological and neurochemical studies of some anxiety states